The evaluation of traffic operation based on travel time study - Guanning, Xu (2014)
Travel time and delay studies are the most popular methods which are used by engineers and planners to evaluate transportation facilities and plan improvement. Because of that the travel time and delay studies provide the necessary data to determine the average travel time and delay. In this research, the first objective is to identify problem on facilities of the study area, floating car method will be used to achieve this objective. Based on the floating car method, travel time, traffic volume and space mean speed is clear shown. The results show that the traffic volume on the road will directly influence in speed and travel time.. Another objective is to assess the consistency of space mean speed generated between floating car method and average speed method. The T-test will be used to compare the space mean speed between floating car method and average speed method. The results showed that the main problem on this road is traffic signals, and the space mean speed between these two method were not significantly different based on traffic volume in vph at 95% confidence interval.